Measuring Learned Helplessness: A Psychometric Approach (2009)
"Learned helplessness, a well established principle in Psychology is a cognitive state of an individual that makes' him/her believes that nothing he does can change his/her situation. Owing to the absence of a direct psychometric based measure of learned helplessness, this study developed a scale to measure the construct and assess individual's tendency to develop learned helplessness using 500 randomly selected participants. This is a 6-item self-report scale in the Likert format and with 5-point response options ranging from strongly disagree (1) to strongly agree (5). The scale yielded a Cronbach Alpha of 0.69, Spearman-Brown Coefficient of 0.66 and Guttman Split-Half Reliability Coefficient of 0.65. Factor analysis using Principal Component Analysis (PCA) showed that all the items loaded as one factor with eigenvalue of 2.37. From the findings, it was concluded. that this scale is useful in measuring the cognitive tendency of individuals to develop learned helplessness in a general population. "